The form and function of quoting in digital media. (March 2015) - Puschmann, Cornelius
Abstract: In this article, we discuss the function of quoting and information sharing in social media services and argue that certain aspects of quoting point to similarities with oral culture, where the social functions of sharing complement the aim to inform or disseminate information. We approach the issue by first providing a brief historical account of content sharing practices from the early days of the Internet to the contemporary social media environment, in which content sharing is both prevalent and facilitated by platform architecture. We then conduct an exploratory quantitative content analysis of three Twitter hashtags relating to different topics, and link their structural variation to the different content sharing practices prevalent in them. We conclude by arguing that the social use of quotation in social media discourse can be a predictor of community structure, but that the degree to which this is the case differs locally. Highlights: Digital media has made content reproduction much simpler and cheaper. Sharing and retweeting are used to indicate affiliation, express support, and manage relationships. Communities can form around topical Twitter hashtags. Different conventions emerge around content sharing in different communities.